2020
DOI: 10.1136/ijgc-2020-001379
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment for patients with FIGO stage I uterine serous carcinoma confined to the endometrium

Abstract: ObjectivesThe role of adjuvant treatment for early-stage uterine serous carcinoma is not defined. The goal of this study was to investigate the impact of adjuvant treatment on survival of patients with tumors confined to the endometrium.MethodsPatients diagnosed with stage I uterine serous carcinoma with no myometrial invasion between January 2004 and December 2015 who underwent hysterectomy with at least 10 lymph nodes removed were identified from the National Cancer Database. Adjuvant treatment patterns defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Recent data from PORTEC-3 study proved the survival benefit of chemotherapy addition in uterine serous carcinomas [ 12 , 40 ]. Similar results were obtained from the retrospective study of Nasioudis et al for early-stage USC [ 41 ]. Additionally, our findings accentuate the diversity of treatments and their combination used in the adjuvant setting in this patients’ cohort, which are consistent with previous studies in other countries [ 42 , 43 ] and reflect the corresponding treatment options suggested by international guidelines [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Recent data from PORTEC-3 study proved the survival benefit of chemotherapy addition in uterine serous carcinomas [ 12 , 40 ]. Similar results were obtained from the retrospective study of Nasioudis et al for early-stage USC [ 41 ]. Additionally, our findings accentuate the diversity of treatments and their combination used in the adjuvant setting in this patients’ cohort, which are consistent with previous studies in other countries [ 42 , 43 ] and reflect the corresponding treatment options suggested by international guidelines [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Also, more patients in the observation group had government insurance (compared with private insurance) which could explain the difference in overall survival. 10 With regards to lymph node staging, a recent expert review has concluded that SLN evaluation is adequate for the staging of Original research uterine serous carcinoma. Indeed, the review confirms that accumulating data support the safety and effectiveness of SLN mapping for apparent early-stage uterine serous carcinoma.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%
“…7 There have been a few retrospective studies with a limited number of patients studying those precise cases. [8][9][10][11][12][13][14][15][16][17] At our center, most patients do not receive adjuvant treatment after surgery.…”
Section: Original Researchmentioning
confidence: 99%
“…There is a paucity of data on adjuvant treatment for stage IA serous and clear cell carcinoma without myometrial invasion and/or occurring in a polyp. In a recent retrospective analysis from the National Cancer Database on 1709 patients with serous carcinoma confined to the myometrium, 5-year OS was 82% for those who had no adjuvant therapy, 85% for those who received adjuvant radiotherapy, and 91% for those who received adjuvant chemoradiation or chemotherapy alone [40]. We do not yet have sufficient data to uniformly recommend chemotherapy for stage I noninvasive serous endometrial carcinoma.…”
Section: Adjuvant Therapy and The Role Of Sentinel Lymph Node Mappingmentioning
confidence: 89%